Analisis Strategi Pemasaran Bank Syariah di Indonesia - Rusmini, Rusmini; Lestari, Dian; Haresma, Aprilia (INAIFAS Press, 2023)
Marketing is often also identified with Marketing is also synonymous with products that are full of promising deals but Tested whether this product is in accordance or not with what has been marketed. It is mandatory to prove by sharia sales management that the product is a product that does not manipulate. Because in sharia sales, good behavior is an important point that is marketed. This is what conventional sales often do not do, because the products marketed do not meet expectations. The purpose of this research is to analyze the marketing strategy of Islamic banks, so that people can use Islamic bank products.